HUBUNGAN GAYA KEPEMIMPINAN KEPALA PUSKESMAS DENGAN MOTIVASI KERJA PEGAWAI DI PUSKESMAS HAEKTO KECAMATAN NOEMUTI TIMUR. - Berkanis, Appolonaris Tomas; Nokas , Primus Yudarius; Muskananfola , Istha Leanni (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
The leadership style of the head of the community health center influences work motivation, work quality and employee performance in terms of providing health services to individuals, families, groups and communities. This research aims to determine the relationship between the leadership style of the head of the community health center and the work motivation of employees at the Haekto Community Health Center, East Noemuti District. The method used in the research was analytical observational with a cross-sectional design. The research was conducted from 18 September to 18 October 2023. The respondents in this study were 49 employees of the Haekto Community Health Center who met the inclusion criteria, namely 1. Willing to be respondents, 2. Working period > 1 year. The sampling technique used was total sampling with data collection using a questionnaire sheet. Data were analyzed using univariate analysis and bivariate analysis. The results of this research show that the leadership style of the head of the community health center is in the ideal category (81.6%), the work motivation of the community health center employees is in the high category (71.4%). The results of bivariate analysis using chi-square show that there is a relationship between the leadership style of the head of the community health center and employee work motivation at the Haekto Community Health Center East Noemuti District (P-value = 0.000). And it is hoped that this research will be an input in improving the leadership style of the head of the community health center in increasing employee work motivation at the Haekto Community Health Center, East Noemuti District.